An Effort of Mutation Breeding by Oryzalin and Gamma Rays on Wild Raspberry (Rubus sp.) in Cibodas Botanical Garden - Muhammad Imam Surya; Lily Ismaini; Destri Destri; Suluh Normasiwi (Biosaintifika: Journal of Biology & Biology Education, 2016)
Currently, Cibodas Botanical Garden (CBG) has a domestication programme of wild raspberries (Rubus sp.) from Indonesia mountain forest. One of the activities in the domestication programme is fruit breeding. In order to improve the quality of wild raspberry, two mutagens i.e. chemical (oryzalin) and physical (gamma rays) mutagens were used in the breeding programme. Moreover, seed of wild raspberries from the collection of CBG were used in the programme of mutation breeding.  The results showed that each species of wild raspberries has different response on the mutagen. Percentage of seed germination were affected by mutagen of oryzalin and gamma rays. Rubus fraxinifolius and Rubus rosifolius seeds were still able to germinate after treated by 100 µM of oryzalin. In the other hand, with increase in radiation above 300 Gy a reduction in percentage of germination was observed in M1 generation of Rubus lineatus and Rubus chrysophyllus.How to CiteSurya, M. I., Ismaini, L., Destri, D. Normasiwi, S. (2016). An Effort of Mutation Breeding by Oryzalin and Gamma Rays on Wild Raspberry (Rubus spp.) in Cibodas Botanical Garden. Biosaintifika: Journal of Biology Biology Education, 8(3), 331-335.